ScandiSent - Språkbanken Text (University of Gothenburg, 2024)
You can find more information on the project's GitHub page.

Mer information finns på projektets GitHub-sida.
ScandiSent
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik